Long Noncoding RNA IGFBP7-AS1 Promotes Odontogenesis of Stem Cells from Human Exfoliated Deciduous Teeth via the p38 MAPK Pathway - Dan Wang; Ningxin Zhu; Fei Xie; Man Qin; Yuanyuan Wang (Hindawi Limited, 2022)
Stem cells from human exfoliated deciduous teeth (SHED) are attractive seed cells for dental tissue engineering. Epigenetics refers to heritable changes in gene expression patterns that do not alter DNA sequences. Long noncoding RNAs (lncRNAs) are one of the main methods of epigenetic regulation and participate in cell differentiation; however, little is known regarding the role of lncRNAs during SHED odontogenic differentiation. In this study, RNA sequencing (RNA-seq) was used to obtain the expression profile of lncRNAs and mRNAs during the odontogenic differentiation of SHED. The effect of IGFBP7-AS1 on odontogenic differentiation of SHED was assessed by alkaline phosphatase (ALP) staining, alizarin red S (ARS) staining, quantitative reverse transcription PCR (qRT-PCR), Western blot, and in vivo. The level of p38 and p-p38 protein expression was examined by Western blot, and the result was verified by adding the p38 inhibitor, SB203580. The expression profiles of lncRNAs and mRNAs were identified by RNA-seq analysis, which help us to further understand the mechanism in odontogenesis epigenetically. IGFBP7-AS1 expression was increased during odontogenic differentiation on days 7 and 14. The ALP staining, ARS staining, and expression of odontogenic markers were upregulated by overexpressing IGFBP7-AS1 in vitro, whereas the expression of osteogenesis markers was not significantly changed on mRNA level. The effect of IGFBP7-AS1 was also verified in vivo. IGFBP7-AS1 could further positively regulate odontogenic differentiation through the p38 MAPK pathway. This may provide novel targets for dental tissue engineering.